ENGLISH YOUTUBE CHANNEL IN ENHANCING STUDENTS’ SPEAKING SKILL - Yunda Lestari (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2019)
This study was aimed at whether YouTube English Channel can significantly enhance the students’ speaking skill at the second semester students of Management Study Program of Economic Faculty in the academic year 2018/2019, University of Baturaja.Quasi experimetal method was used in this study. This study employed second semester students of  Management Study Program of Economic Faculty, University of Baturaja with the total number of the population was 132 students. The sample of the study was 64 students and it was found that the value of Sig.= 0,000 less than the significance level (α=0,05)  so it meant that there was a great correlation between the score of pre-test and post-test. Then, the value of t-obtained = 9,057 which means   more than value of t-table = 2,042 with df = 32, and the value of sig.(2 tailed) = 0,000 less than the significance level (α=0,05).    It can be concluded that there was a significant difference in speaking skill before and after treatment. It was believed that YouTube English Channel could enhance students’ speaking skill.